Design and Analysis of 8-bit Vedic Multiplier in 90nm Technology using GDI Technique - Sharma, Sandesh; Sharda, Vangmayee (International Journal of Engineering and Technology, 2018)
Vedic mathematics is an old mathematics which is more effective than other mathematic procedures. Vedic maths is utilized as a part of numerous applications, for example, hypothesis of numbers, compound duplications, squaring, cubing, square root and solid shape root and so on. Absolutely there are 16 sutras and 14 sub-sutras in Vedic maths. Among those sutras, just 3 sutras and 2 sub-sutras are utilized for augmentation. Multiplier is a very important part of a microprocessor as multiplication is performed continuously in all calculative procedures. This paper is in importance of a 8-bit multiplier designed in 90 nm technology. Urdhva-Tiryakbyham is the sutra that is used for multiplication in Vedic mathematics. Actualizing the different scientific operations utilizing Vedic Mathematics causes us Â accomplish better speed, bring down unpredictability and higher execution.[2] The technique used is Gate Diffusion Input (GDI) which is a more refined way to design a circuit which less complex than circuits designed by other techniques. Â Â